Navigating non-alcoholic fatty liver disease (NAFLD): understanding the correlation between hepatic vein and portal vein doppler indices and fatty liver grades - Muhammad Salman Rafique; Sahar Zulfiqar, Sahar Zulfiqar; Fatima Sehar, Fatima Sehar; Bushra Bilal, Bushra Bilal; Kainat Khan (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the association of fatty liver ultrasound grade with hepatic venous waveform, hepatic vein damping index and portal vein pulsatility index. Method: The cross-sectional, prospective, analytical study was conducted at the Radiology Department of the Pakistan Kidney and Liver Institute and Research Centre, Lahore, Pakistan, from January 1 to June 30, 2023, and comprised patients who underwent ultrasound scans with a low-frequency curvilinear transducer. Data was collected on fatty liver grade, middle hepatic vein waveform, middle hepatic vein damping index and portal vein pulsatility index. The relationship of fatty liver grades with hepatic vein waveform, hepatic vein damping index and portal vein pulsatility index. Data was analysed using SPSS 27. Results: Of the 45 patients, 26(57.88%) were females and 19(42.22%) were males. The overall mean age was 43.16±11.55 years. Among the patients, 36(80%) had a grade-1 fatty liver, while 9(20%) had a grade-2 fatty liver. Mean middle hepatic vein damping index between grade 1 and grade 2 fatty liver patients was significant (p<0.001). The mean portal vein pulsatility index of grade 1 fatty liver patients was significantly different from grade 2 patients (p<0.001). Fatty liver sonological grade had a moderate and direct relationship with middle hepatic vein damping index (r=0.652), but an inverse relationship was observed between fatty liver sonological grade and portal vein pulsatility index (r=-0.427). Conclusion: Significant correlations existed between ultrasound fatty liver grade and hepatic vein waveforms, hepatic vein damping index and portal vein pulsatility index. Key Words: Non-alcoholic fatty liver disease, Hepatic veins, Portal vein, Ultrasound.